Temporal and spatial changes in the composition and structure of helminth component communities in European eels Anguilla anguilla in an Adriatic coastal lagoon and some freshwaters in Italy - Dezfuli B. S.; Lui A.; Giari L.; Castaldelli G.; Lanzoni M.; Rossi R.; Kennedy C. R.; LORENZONI, Massimo (Parasitology Research, 2014)
The composition and diversity of the helminth component communities in eels Anguilla anguilla were determined in three separate localities in Italy: an Adriatic coastal lagoon, Comacchio and two freshwater localities, the River Po and the Lake Piediluco. Data from Comacchio lagoon were analysed over 15 years to determine whether community composition and diversity changed significantly overtime. The community was species rich (nine species, all marine except Proteocephalus macrocephalus ) and was dominated by a suite of digeneans: Deropristis inflata , Helicometra fasciata, Lecithochirium musculus and Bucephalus anguillae. The community showed little change in composition over the period, but the relative abundance and dominance of the species did alter. By contrast, the component communities in the freshwater localities were species poor and the dominant specieswere freshwater acanthocephalans, Pomphorhyncus laevis in River Po and Acanthocephalus rhinensis in Lake Piediluco. The helminth community of Lake Piediluco with five species was richer than that of the River Po with only three species, but was poorer than that of Comacchio lagoons. Similarity indices between samples from Comacchio were high; between the lagoon and the freshwater localities and between the two freshwater localities, similarity indices were very low. Helminth component community structure in coastal lagoons was comparable across Europe. The helminth community in the River Po was similar to those in the River Tiber and other European rivers whilst that in Lake Piediluco was similar to that in other European lakes. Levels of the pathogenic Anguillicoloides crassus in swim bladders were consistently lower in prevalence and abundance in the coastal lagoons than in freshwater localities. This suggests that this parasite may have little impact on migrating eels if they are indeed primarily of marine origin and so it may be of little importance in the recent decline of eel populations throughout Europe.